An Iterative, Multidisciplinary Approach to Studying Digital Play Motivation: The Model of Game Motivation. (May 2015) - Herodotou, Christothea; Winters, Niall; Kambouri, Maria
The aim of this article is to present the methodological approach adopted for the development and iteration of the Model of Game Motivation (MGM), a conceptual model explaining digital play motivation. A multidisciplinary, mixed-methods research design was deployed for the empirical iteration of the model. This choice was reinforced by the critical review of related literature, which revealed that a combination of evidence from multiple disciplines (psychology, sociology, and technology) could contribute to a more comprehensive understanding of play motivation. An iterative, hypothesis-testing research design was the strategy used to conduct multidisciplinary, mixed-methods research. The initial, theoretical version of the MGM was iterated twice, resulting in a thoroughly developed, empirically grounded version that requires future validation. The value of this approach lies in the fact that it provides to game design stakeholders a methodological tool for understanding play motivation as a multifaceted activity, which could inform their practices.